A new species of Lesteva Latreille (Coleoptera, Staphylinidae, Omaliinae) from Zhejiang, East China - Ma, Wen-Li; Li, Li-Zhen (Zootaxa, 2012)
Lesteva brevimacula Ma & Li, sp. nov. from northern Zhejiang Province, East China, is described. Its external and male sexual characters are illustrated. The latest key to Chinese Lesteva is modified to include the new species.